Wpływ parametrów zakłócających na pracę skrzyni biegów wyposażonej w przekładnię CVT - Radzymiński, Bartosz; Pawelski, Zbigniew (Wydawnictwa Politechniki Łódzkiej, 2015)
The paper presents mechanical scheme of transmission from Nissan Micra vehicle equipped with a push belt. For the tested gearbox test bench has been prepared in which it was possible to simulate the load conditions and adjust pressures responsible for the transmission operation through open and closed systems using PID controllers.
Keywords: mechaniczna skrzynia biegów; przekładnia CVT; mechanical gearbox; gear cvt